Communion table - Ghosh, Ayan (2023)
Till the mid-1950s, St. Thomas Cathedral had a huge British congregation headed by an English priest. With the steady departure of the British population and the emigration of Anglo-Indians from India, the congregation now comprised mostly Indian Christians. The church is headed by the Anglican Bishop of Bombay (Mumbai).